Oral Hygiene Behavior of Croatian Adolescents during Fixed Orthodontic Treatment: A Cross-sectional Study - Martina Čalušić Šarac; Sandra Anić Milošević; Željana Matošić; Marina Lapter Varga (University of Zagreb. School of Dental Medicine, 2021)
Objective: To investigate the impact of fixed orthodontic treatment on adolescents' oral hygiene behavior and to examine their food consuption during fixed orthodontic treatment, as well as their motivation to maintain oral hygiene. Materials and methods: This research was carried out in a form of a survey questionnaire consisting of 23 questions. The sample comprised 170 adolescent patients aged from 11 to 19 who underwent the fixed orthodontic treatment at the Orthodontic Clinic of the Zagreb University Hospital Centre. Results: The orthodontic appliance did not interfere with the patients' maintenance of oral hygiene, but it made the consumption of certain foods more difficult. Most adolescents brushed their teeth twice a day, using medium-soft brushes (35%). Regarding additional oral hygiene aids, 72.4% of the respondents used interdental brushes, more than 50% of the respondents used antiseptic mouthwashes for mouth rinsing, whereas only 31.2% of the tested population used dental floss (4.1% of which daily). The respondents were highly motivated to maintain oral hygiene by their orthodontists (96.5%), but only a small number of the respondents were informed about the importance of an adequate diet while undergoing a fixed orthodontic treatment. Conclusion: Orthodontists should provide their patients with detailed instructions on hygiene maintenance and adequate diet during orthodontic treatment to minimize negative side effects of the fixed orthodontic treatment. Patients should be motivated upon each follow-up examination and encouraged to use as many oral hygiene aids in their daily routines as possible.